2014
DOI: 10.1089/jmf.2013.0044
|View full text |Cite
|
Sign up to set email alerts
|

AnIn VitroandIn VivoStudy of the α-Amylase Activity of Phaseolamin

Abstract: We evaluated the polypeptide profiles, inhibition of human salivary a-amylase activity, and hemagglutination properties of a commercial phaseolamin sample. We also performed an in vivo assay to investigate the effects of a commercial phaseolamin treatment (100, 500, or 1500 mg/kg) over 20 days on the glycemia, body weight, and serum biochemical parameters (total cholesterol, triglycerides, alanine aminotransferase, and aspartate aminotransferase) of nondiabetic and streptozotocin-induced diabetic rats. The in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 33 publications
0
8
0
5
Order By: Relevance
“…Animals were fasted for another 90 min after the injection. Ten days after the STZ injection, rats with a fasting blood glucose level greater than 250 mg/dL were used for subsequent experiments [ 16 , 17 ]. Body weight and blood glucose levels were monitored in animals undergoing the different treatments (water, glibenclamide, and V .…”
Section: Methodsmentioning
confidence: 99%
“…Animals were fasted for another 90 min after the injection. Ten days after the STZ injection, rats with a fasting blood glucose level greater than 250 mg/dL were used for subsequent experiments [ 16 , 17 ]. Body weight and blood glucose levels were monitored in animals undergoing the different treatments (water, glibenclamide, and V .…”
Section: Methodsmentioning
confidence: 99%
“…The active polyphenols present in this extract impart a blood glucose-lowering effect via insulin sensitization as well as inhibition of α-amylase and α-glucosidase activities (Ramachandran and Rajasekaran, 2014). Commercial phaseolamin, which has high α-amylase inhibitory ability, can reduce the blood glucose levels in streptozotocin-induced diabetic rats; therefore, it possesses therapeutic potential for the treatment or prevention of the complications of diabetes (De Gouveia et al, 2014). According to these results, substances with the ability to inhibit the activity of α-amylase and/or α-glucosidase may also possess anti-hyperglycemic potential via alleviation of the high blood glucose status in diabetic individuals.…”
Section: Introductionmentioning
confidence: 99%
“…De Gouveia et al found that patients treated with phaseolamin did not have any decrease in body weight, but this study was conducted for only 20 days and therefore, follow-up bias could have affected the conclusions of this study. 99 The use of phaseolamine as an antihyperglycemic is contended. Oliveira et al found that phaseolamin can be used to control diabetes due to its anti-hyperglycemic effect.…”
Section: Bacterial Amylasementioning
confidence: 99%